Nutritional Labeling Today: What Consumers Want - and What They Understand - Kornelia Hagen (Weekly Report, 2010)
Findings from consumer surveys and studies about nutritional labeling tend to be hard to compare, because the methodologies they use and questions they address are quite varied. Nevertheless, by evaluating these studies, we can obtain a good overview of existing nutritional labeling systems and consumer preferences. The present background article offers an overview of the studies frequently cited in current debates.
Keywords: D3; D11; 330; Labelling systems; Traffic light labelling